1997
DOI: 10.1002/(sici)1097-0223(199701)17:1<47::aid-pd19>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Alpha-Fetoprotein and Epithelial Tumour Marker Concentrations Are Not Increased by Fetal Sacrococcygeal Teratoma

Abstract: Maternal serum alpha‐fetoprotein (AFP) and total beta‐human chorionic gonadotrophin (hCG) concentrations were measured at the 15th gestational week in ten pregnancies complicated by fetal sacrococcygeal teratoma. The findings corresponded to those in normal pregnancies. Similarly, third‐trimester concentrations of cancer antigen 12‐5, tumour‐associated trypsin inhibitor, and the amino‐terminal propeptide of type III procollagen in the maternal serum were not significantly elevated. Histologically mature and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
6
1
1
Order By: Relevance
“…Hunter et al reported that plasma AFP levels of a patient with pediatric retroperitoneal teratoma correlated with tumor immaturity (Hunter et al 2009). On the other hand, there was one report that maternal serum AFP concentrations were not increased by fetal sacrococcygeal teratoma (Kirkinen et al 1997). In our Case 2 with immature teratoma, both maternal serum and amniotic AFP were markedly increased.…”
Section: Discussioncontrasting
confidence: 56%
“…Hunter et al reported that plasma AFP levels of a patient with pediatric retroperitoneal teratoma correlated with tumor immaturity (Hunter et al 2009). On the other hand, there was one report that maternal serum AFP concentrations were not increased by fetal sacrococcygeal teratoma (Kirkinen et al 1997). In our Case 2 with immature teratoma, both maternal serum and amniotic AFP were markedly increased.…”
Section: Discussioncontrasting
confidence: 56%
“…Similarly, in malignant teratomas, elevated levels of alphafetoprotein (AFP) and hCG have been documented. On the other hand, a study of 10 patients with a 15 th gestational week fetal SCT showed no increase in AFP or hCG levels, whether the teratoma was malignant or nonmalignant [8]. Therefore, it is difficult to determine if the increase in hCG in our patient was a result of the SCT.…”
Section: Discussionmentioning
confidence: 68%
“…SCT is the most common fetal tumor, but is a rare condition occurring in only one in 35,000 live births [7,8]. These tumors are benign in 90% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Dadurch könnte auch die Optimierung bezüglich des geburtshilflichen Managements sowie der operativen Nachsorge des Neonaten erreicht werden. Bestimmungen von Serummarkern wie aFP sowie bhCG bei der Mutter haben sich in der Diagnosestellung von ST leider nicht bewähren können [18]. Blutflussumleitung in Richtung Tumor und Plazenta bestand, die ihrerseits aufgrund der Herzbelastung zu der vorliegenden Plazentahypertrophie und dem Hydrops fetalis führte.…”
Section: Pränataldiagnoseunclassified